2020
DOI: 10.1029/2020ja028307
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric Response at Conjugate Locations During the 7–8 September 2017 Geomagnetic Storm Over the Europe‐African Longitude Sector

Abstract: This paper focuses on unique aspects of the ionospheric response at conjugate locations over Europe and South Africa during the 7-8 September 2017 geomagnetic storm including the role of the bottomside and topside ionosphere and plasmasphere in influencing electron density changes. Analysis of total electron content (TEC) on 7 September 2017 shows that for a pair of geomagnetically conjugate locations, positive storm effect was observed reaching about 65% when benchmarked on the monthly median TEC variability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 41 publications
0
13
5
Order By: Relevance
“…The day-to-day variability is removed with the mean quiet level (f o F 2 (q)) obtained using the data acquired during the five International Quiet Days (IQDs) of the month. The range of ±20% in Df o F 2 is used by several authors (Habarulema et al, 2020;Matamba et al, 2015, and reference therein) to represent the day-to-day variability, and the deviations outside this range are attributed to the ionospheric disturbances during the geomagnetic storms. The five IQDs used in this work are August 6, 10, 13, 14, and 23, 2018, except for Port Stanley which used September 1, 3, 8, 19, and 20, 2018 It is also used in this work the thermospheric column-integrated [O]/[N 2 ] from the Global Ultraviolet Imager (GUVI) spectrograph of the TIMED satellite (http://guvitimed.jhuapl.edu/; Christensen et al, 2003;Paxton et al, 2005).…”
Section: Of 18mentioning
confidence: 99%
“…The day-to-day variability is removed with the mean quiet level (f o F 2 (q)) obtained using the data acquired during the five International Quiet Days (IQDs) of the month. The range of ±20% in Df o F 2 is used by several authors (Habarulema et al, 2020;Matamba et al, 2015, and reference therein) to represent the day-to-day variability, and the deviations outside this range are attributed to the ionospheric disturbances during the geomagnetic storms. The five IQDs used in this work are August 6, 10, 13, 14, and 23, 2018, except for Port Stanley which used September 1, 3, 8, 19, and 20, 2018 It is also used in this work the thermospheric column-integrated [O]/[N 2 ] from the Global Ultraviolet Imager (GUVI) spectrograph of the TIMED satellite (http://guvitimed.jhuapl.edu/; Christensen et al, 2003;Paxton et al, 2005).…”
Section: Of 18mentioning
confidence: 99%
“…The size of the asymmetry was about 15° in longitude and 10° in latitude. This asymmetry was also studied in (Habarulema et al, 2020). On the contrary, in the East Asian-Australian sector around 120°E longitude, the VTEC increased in the northern mid-latitude region (20°∼30° MLAT), while decreased in the conjugate southern hemisphere.…”
Section: Observationsmentioning
confidence: 84%
“…A double‐dip geomagnetic storm occurred on September 7–8, 2017, and has received much attention (Aa et al., 2018, 2019; Habarulema et al., 2020; Imtiaz et al., 2020; Jimoh et al., 2019; Jin et al., 2018; Lei et al., 2018; Mosna et al., 2020; Rout et al., 2019; Shen et al., 2018; Wang et al., 2019; Xiong et al., 2019; Zhang et al., 2019). Figures 1a–1f show the By and Bz components of the IMF in the geocentric solar magnetospheric (GSM) coordinates (IMF By and Bz), solar wind speed, proton number density, dynamic pressure, and the SYM‐H index during September 7–8, 2017.…”
Section: Observationsmentioning
confidence: 99%
“…Past studies have shown that these events were marked by changes in ionospheric current using ground‐based magnetometer (Owolabi et al., 2020), reduction in background sky noise level observed with SuperDARN (Chakraborty et al., 2019) and TEC response to the SFs and GS of 6–9 September (Chakraborty et al., 2021). Others researchers have focused on the variations in thermospheric composition, electric field, and ionospheric irregularities (Akala et al., 2020), changes in the plasmasphere using in situ observations of electron density (Obana et al., 2019) as well as hemispheric difference over the European‐East African sector (Habarulema et al., 2020). Furthermore, the CMEs of 6–7 September have been modeled (Werner et al., 2019) while the variation in the thermosphere and ionosphere using the Thermosphere Ionosphere Electrodynamics General Circulation Model have been presented (Qian et al., 2020).…”
Section: Introductionmentioning
confidence: 99%